2020
DOI: 10.23937/2469-567x/1510058
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Malaria and Some Opportunistic Infections in Human Immunodeficiency Virus/Acquired Immune Deficiency Syndrome (HIV/AIDS) Patients with CD4 Below 200 in Faith Alive Hospital, Jos, Plateau State, Nigeria

Abstract: The human immunodeficiency virus (HIV) infection leads to Acquired Immunodeficiency Syndrome (AIDS) resulting to a progressive decline in the immune system of people living with HIV/AIDS (PLWHA) making them susceptible to a variety of opportunistic infections which eventually leads to death. This study aimed at determining the prevalence malaria and some opportunistic infections in HIV/AIDS patients with CD4 count below 200 attending Faith Alive Hospital, Jos, Plateau State. The testing for opportunistic infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…A study conducted in Southwest Ethiopia also reported that malaria was more prevalent among HIV-positive individuals within a similar age range (25–34 years). 31 Studies in Jos, Nigeria, 4 Europe, 6 and Beira, Mozambique 22 have similarly reported that the prevalence of parasitaemia among HIV patients is usually among this age group. On the other hand, studies conducted on the mainland of Tanzania 32 and in Nankoma, Uganda 33 dispute this finding, indicating that the occurrence is typically highest among those under the age of 20, while another in Cross River State, Nigeria discovered that age has no bearing on this.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…A study conducted in Southwest Ethiopia also reported that malaria was more prevalent among HIV-positive individuals within a similar age range (25–34 years). 31 Studies in Jos, Nigeria, 4 Europe, 6 and Beira, Mozambique 22 have similarly reported that the prevalence of parasitaemia among HIV patients is usually among this age group. On the other hand, studies conducted on the mainland of Tanzania 32 and in Nankoma, Uganda 33 dispute this finding, indicating that the occurrence is typically highest among those under the age of 20, while another in Cross River State, Nigeria discovered that age has no bearing on this.…”
Section: Discussionmentioning
confidence: 98%
“…Opportunistic infections occur more frequently and with greater severity in individuals with compromised immune systems, such as those positive for HIV. 4 Opportunistic infections are less prevalent today than during the early stages of HIV and AIDS, owing to improved medications that reduce HIV viral load and strengthen the immune system. 5 However, many people living with HIV continue to develop opportunistic infections, because they are unaware of their HIV status, are not on treatment, or their treatment does not keep their viral load low enough for their immune system to fight infections.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation